2019
DOI: 10.17140/oroj-6-138
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Sleep, Sedentary Behavior, and Physical Activity in Young Adults

Abstract: PurposeWhile there are some studies on sleep and physical activity, little is known regarding the associations between sleep and sedentary behavior. This study investigated the associations between sleep, sedentary behavior, and physical activity among young adults. MethodsCross-sectional data from 124 undergraduate students were included in the analysis (age=21±1 years). Both accelerometer-based and self-report assessments of sleep were included; physical activity and sedentary behavior were assessed by accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…Physical activity has been associated with quality of sleep that reduces daytime sleepiness. In a study conducted by Hsu et al (2019), the findings revealed that high school students who engaged in physical activity for more than 3.5 hours per week had improved sleep quality. Additionally, Ströhle (2008) suggests that getting at least 60 minutes of daily physical activity is associated with adequate quality sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been associated with quality of sleep that reduces daytime sleepiness. In a study conducted by Hsu et al (2019), the findings revealed that high school students who engaged in physical activity for more than 3.5 hours per week had improved sleep quality. Additionally, Ströhle (2008) suggests that getting at least 60 minutes of daily physical activity is associated with adequate quality sleep.…”
Section: Introductionmentioning
confidence: 99%
“…They have been influenced by various interdependent factors regarding the time-lapse over a day. Therefore, they are modifiable [ 3 ] throughout the different life phases. The term habitual human behaviors (HHB) was adopted due to possible concepts counterpoints, considering the definition of sleep as a behavioral, reversible, and cyclic state characterized by relative immobility and increased threshold of responses to external stimuli [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent randomized controlled trial examined the effects of SB on sleep quality by randomly assigning active young adults into a SB intervention (increasing sedentary behavior intentionally) or a control group for one week, and found that young adults who increased their time in SB experienced significant decreases in sleep quality [16]. In addition, compiling research has indicated significant associations between SB, sleep quality, and obesity [22][23][24][25]. One recent study evaluated college students' sleep quality and body fat mass, and found that poor sleep efficiency was strongly associated with increased fat mass in both men and women [23].…”
Section: Introductionmentioning
confidence: 99%